2013
DOI: 10.1007/s11427-013-4461-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of phosphorus deficiency and exogenous auxin on root morphological and physiological traits in white lupin (Lupinus albus L.)

Abstract: White lupin (Lupinus albus) exhibits strong root morphological and physiological responses to phosphorus (P) deficiency and auxin treatments, but the interactive effects of P and auxin in regulating root morphological and physiological traits are not fully understood. This study aimed to assess white lupin root traits as influenced by P (0 or 250 mol L 1) and auxin (10 8 mol L 1 NAA) in nutrient solution. Both P deficiency and auxin treatments significantly altered root morphological traits, as evidenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The specific impacts of P deficiency on root growth have been identified in diverse species such as L. albus, A. thaliana, P. trifoliate, Glycine max , and Cucurbita pepo ( Sánchez‐Calderón et al., ; Wang et al., ; Cao and Chen , ; Tang et al., ; Cao et al., ). For example, P deficiency significantly reduced the length of the principal root and increased the number and density of lateral roots in L. albus ( Tang et al., ). G. max under P deficiency exhibited significantly larger root length, root surface area, and root volume when compared to those under normal P supply ( Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific impacts of P deficiency on root growth have been identified in diverse species such as L. albus, A. thaliana, P. trifoliate, Glycine max , and Cucurbita pepo ( Sánchez‐Calderón et al., ; Wang et al., ; Cao and Chen , ; Tang et al., ; Cao et al., ). For example, P deficiency significantly reduced the length of the principal root and increased the number and density of lateral roots in L. albus ( Tang et al., ). G. max under P deficiency exhibited significantly larger root length, root surface area, and root volume when compared to those under normal P supply ( Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus deficiency can significantly inhibit the growth of most plant organs, while promoting the growth of lateral roots. It has been reported that P deficiency significantly alters the morphological traits of Lupinus albus roots, such as reduced taproot length, increased number and density of first‐order lateral roots, and enhanced cluster‐root formation ( Tang et al., ). Phosphorus is an important signal for postembryonic root development and P deficiency increases the root hair elongation of Arabidopsis thaliana ( Sánchez‐Calderón et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These relatively small morphological responses of Lupinus albus to P application suggested that effective mobilization of rhizosphere P (physiological response) is more resource-efficient than extending roots (morphological response) to get P from far away (Shen et al, 2011). Indeed, cluster roots ( Supplementary Figure S1 ) enhanced root exudation, thus enhancing the root physiological responses (Shen et al, 2005; Tang et al, 2013b). …”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions of all these studies mainly focused on independent changes in either root morphological or physiological parameters, such as shoot biomass or carboxylate exudation (Hoffland et al, 1989a,b; Tadano et al, 1993; Neumann and Römheld, 1999; Nuruzzaman et al, 2005; Li et al, 2010; Rose et al, 2010; Vu et al, 2010; Maltais-Landry, 2015), or some correlation between these parameters (Shen et al, 2003; Watt and Evans, 2003; George et al, 2006; Pearse et al, 2007; Zhang et al, 2009). In this study, the PCA method was used as reported before (Tang et al, 2013b) to calculate the relative contribution of the root morphological or physiological response parameter scores to P acquisition, and then quantitatively evaluate the relationship between root morphological and physiological traits in response to P supply and soil types ( Figures 8 and 9 ). Zea mays and Triticum aestivum had higher root morphology scores (strong response in root/shoot ratio, total root length and SRL; Figures 2 and 3 ) and low physiology scores (low exudation of APase and carboxylates and consequently low P-acquisition efficiency; Figures 4 and 7 ), exhibiting greater changes in the root morphology scores to P supply in the two soil types compared with the legume species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation